Development of Video Tutorials for Simple Distillation Tools for Making Essential Oils in Junior High Chemistry Course - Listra, Irene Yudea; Hairida, Hairida; Rasmawan, Rahmat; Enawaty, Eny; Masriani, Masriani (Universitas Pendidikan Mandalika, 2024)
This study aims to develop a video tutorial for simple distillation equipment for making essential oils that is suitable for use in junior high school chemistry courses. The research is a development research using the Design Thinking approach. The Design Thinking approach includes five steps, namely: empathic, definition, idea, prototype, and test. The instruments used in this study are student response questionnaires and validity on video tutorials for simple distillation equipment for making essential oils. The results of validation and student response to the video were analyzed using a Guttman scale and obtained a percentage of validation of the feasibility of media design 100% with a very valid category, articulation and intonation 100% with a very valid category, operation 100% with a very valid category, and suitability of material with sub-CPMK 100% with a very valid category. The percentage in the response test, namely the media display indicator 96.8% with a very good category, 100% operation with a very good category, and 98.95% usefulness with a very good category. Thus it can be concluded that the results of the analysis of video tutorial development are worth testing in the learning process.